The Effects of Lemon-Garlic Supplement and Aerobic Exercise on Serum Levels of CRP and Fibrinogen Levels in Overweight Men - M Akbarpour; H Ghobadipour (Armaghane Danesh Bimonthly Journal, 2019)
Background and objective: The development of cardiovascular diseases and mortality caused this study to evaluate the effect of 6 weeks of supplemental diet and aerobic exercise on plasma levels of CRP and fibrinogen in overweight men. Method: 32 non-athletic overweight men from Qom University with a mean age of 31 ± 1.38 years, and body mass index 31.19 ± 4.18 kg / m2, were randomly assigned to four groups (8 subjects), supplemented (8 subjects ), Exercise + complement (7 subjects) and control (n = 10 subjects). The control group did not undergo any training and supplementation during 6 weeks, The exercise group performed 6 weeks aerobic training with an intensity of 60-74% of maximum heart rate and 3 sessions per week. The supplemented group consumed 6 weeks of garlic-Lemon and the exercise + supplement group consumed complementary supplements and aerobic exercise for 6 weeks. Blood sampling was performed to measure CRP and Fibrinogen and general tests including height, weight, fat percentage, waist to hip ratio in two stages before and 48 hours after the last training session in fasting conditions. The t-test was used to examine the differences between groups and one-way ANOVA was used to examine the differences between groups. Results: A significant decrease in fat percentage was observed in the supplementation group (p = 0.035) Also, the results did show decrease significant changes in CRP and fibrinogen in the Exercise + complement and supplemented groups, thus CRP level in the Exercise + complement group was 27% and the supplementation group was 26% and the fibrinogen level in the Exercise + complement group was 38% and in the supplemented group 29% has decreased. Discussion: According the decrease significant in inflammatory levels in this study, but a significant reduction in the percentage of these variables was observed in the study, it seems that the implementation of the garlic-Lemon supplementation protocol can be effective in changing these indices and reduce the risk of cardiovascular disease.